anithaganesh88
anithaganesh88
01-09-2020
Mathematics
contestada
Solve : 3x – 4 = 2(x-1)
Respuesta :
peeptryhxrd
peeptryhxrd
01-09-2020
Answer:
Step-by-step explanation:
Answer Link
aayu0302
aayu0302
01-09-2020
Answer:
x=2
Step-by-step explanation:
3x-4=2(x-1)
=>3x-4=2x-2
=>3x-2x=-2+4
=>x=2
Answer Link
VER TODAS LAS RESPUESTAS ( 43+ )
Otras preguntas
PLEASE HELP!!!! Triangle ABC is translated using the rule (x, y) → (x + 1, y − 4) to create triangle A′B′C′. If a line segment is drawn from point A to point A′
Help with this please! I really confuse and don’t understand.
Find two functions f(x) and g(x) such that h(x) = ( f∘ g)(x) , if h(x) = √ + 5 f(x) = ____________________g(x) = ____________________
Could these triangles be congruent? yes, if ab ≅ de yes, if bc = 7 yes, if ab ≅ ef no, because the hypotenuses must have different lengths
1. What career do the adults in young Mandela’s life plan for him to follow? 2. How do speeches teenage Mandela hears change his view about English rule in Sout
Which are correct representations of the inequality –3(2x – 5) < 5(2 – x)? Select two options. x < 5 –6x – 5 < 10 – x –6x + 15 < 10 – 5x A number li
who was the first president of kenya
If a study determines the difference in average salary for subpopulations of mechanical engineers and civil engineers is NOT significant, then the subpopulation
Prompt Write a paragraph comparing and contrasting the performer's interpretation of "84" to the original text. Explain the effects of the performer's choices i
Read the excerpt from Eleanor Roosevelt’s speech "The Struggle for Human Rights.” As I see it, it is not going to be easy to attain unanimity with respect to ou